The Optimal Incentive Contract Design for Enterprise Employees Based on Principal-Agent Theory - Weihua Duan, Junyan Zhang, Zhichuan Zhu, Guochao Zhang, (Design Engineering, 2020)
Aims at the moral hazard problem caused by the hidden employee effort level due to information asymmetry, the optimal incentive contract was designed, modeled, solved and analyzed for employees under asymmetric information conditions based on the principal-agent theory. Firstly, an optimal incentive contract model was constructed based on the principal-agent theory. Secondly, the model was solved to analyze the effect of each factor’s change to employee's expected utility under the optimal incentive contract in order to obtain the effective motivation and the way for improving the incentive effect. Finally, the corresponding management strategies and suggestions for establishing the optimal incentive contract between enterprises and employees are put forward according to the effective way for solving the optimal incentive contract model.